Detecting Malposition of Coil Couple for Transcutaneous Energy Transmission. Issue 1 (January 2016) - Hu, Liang; Fu, Yang; Ruan, Xiaodong; Xie, Haibo; Fu, Xin
Abstract : Transcutaneous energy transmission technology based on coil coupling is widely required for various wireless powering implanted devices in human body. However, the coupling performance is commonly affected by malposition between coils in practice. It is difficult for users to know the actual position of the implanted receiver coil (RC) and how to realign the transmitter coil (TC) outside the body. This article proposes a detecting method of coil-coupling malposition based on a sensing board with coil array fitted on the TC. In this article, the sensing system and the data processing algorithm separating the sensing coil (SC) signals induced by TC and RC currents, respectively, are introduced. Then, an analytical model formulating the induction effect between the RC and SCs is given. Inverse computation algorithms of the malposition based on the processed sensing data and the induction effect model are presented at last. The proposed method is validated by experiments simulating malposition both in distance and concentricity on an actual coil couple. The results show that the sensing system can provide accurate parameterized guide for users to adjust the installation of the TC for good energy transmission performance.